Răspuns :
(a+b)²=(√6+2√5+√6-2√5)²=(2√6)²=24
(a-b)²=(√6+2√5-√6+2√5)=(4√5)²=80
2)ma=(7+4√3+7-4√3)/2=14/2=7
mg=√(7+4√3)(7-4√3)=√7²-(4√3)²=√49-48=√1=1
4)x²+1/x²=(x+1/x)²-2=7/2-2=3/2
5)a²+b²=(a+b)²-2ab=8²-2·5=64-10=54
6)a²-b²=(a+b)(a-b)
12√6=6√2(a-b)
a-b=12√6/6√2=2√6/√2=2√3
3)se descompune fiecare expresie
a)x²+10x+25+6=(x+5)²+6 x=-5
b)x²-8x+16+17=(x-4)²+17 x=4
(a-b)²=(√6+2√5-√6+2√5)=(4√5)²=80
2)ma=(7+4√3+7-4√3)/2=14/2=7
mg=√(7+4√3)(7-4√3)=√7²-(4√3)²=√49-48=√1=1
4)x²+1/x²=(x+1/x)²-2=7/2-2=3/2
5)a²+b²=(a+b)²-2ab=8²-2·5=64-10=54
6)a²-b²=(a+b)(a-b)
12√6=6√2(a-b)
a-b=12√6/6√2=2√6/√2=2√3
3)se descompune fiecare expresie
a)x²+10x+25+6=(x+5)²+6 x=-5
b)x²-8x+16+17=(x-4)²+17 x=4